Humanizing education reflection on concepts, attributes, roles and sustainability with selected attributes of true believers in the qur’an and sunnah - Abdul Razak, Dzuljastri (Meso Publishing, 2021)
This book compiles written expressions of participants in 2021 KENMS Ibadah Camp with the theme “attributes of true believers in the Quran and Sunnah” in the framework of humanizing education with maqasid al-shariah.